China's arms sales motivations and implications - Byman, Daniel; Cliff, Roger (Rand, 1999)
China's arms sales have become the focus of considerable attention and pose a moderate threat to U.S. interests. Although Chinese sales have fallen in recent years, and Beijing has become more responsible in the transfer of nuclear, biological, and chemical (NBC) technologies, much progress will be needed to curtail China's behavior. Principal recipients of Chinese arms have been Iran, Iraq, Myanmar, North Korea, Pakistan, and Thailand. These countries and others seek Chinese weapons because they are available, cheap, and easy to use and maintain. In addition to missiles, the Chinese are willing to transfer NBC technology. The United States and other countries do have a modest ability to influence Chinese behavior, and China has increasingly wished to be viewed as a responsible world nation. The analysis supports three major findings about China's arms sale behavior: (1) China's arms transfers not motivated primarily to generate export earnings but by foreign policy considerations; (2) China's government has more control over transfers than some have reported: its weapons export system is quite centralized; and (3) China's adherence to international nonproliferation norms is in fact increasing. Nevertheless, Washington must hedge against the likelihood of sales and develop offsets in concert with allies.